Contiguity service constraints for vehicles routing: applications in household refuse collection - Nunes, Ana Catarina; Mourão, Maria Cândida; L. Gouveia; Constantino, Miguel (IO 2013 - 16.º Congresso da APDIO, 2013)
Household refuse collection in urban areas may be modelled by a mixed capacitated arc routing problem or a sectoring-arc routing problem. In this type of real world applications, it is frequently desirable to ensure the contiguity of the service of each vehicle, concentrating their service and avoiding vehicles’ intersection while servicing. However, the contiguity of the links served by a vehicle (trip or sector) is not usually contemplated in the formulations for capacitated arc routing problems over mixed graphs. With this in mind, additional linear constraints are discussed and computational results for benchmark problems are reported.